2011
DOI: 10.1007/s11249-011-9776-8
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Properties of a Mesoscopic Contact with Engineered Surface Roughness

Abstract: Friction between titanium spheres and an artificially structured silicon surface was measured with a friction force microscope. Two spheres with radii of 2.3 lm and 7.9 lm were firmly glued to the tip of the microscope cantilever. A periodic stripe pattern with a groove depth of 26 nm and systematically increasing groove width from 500 nm to 3500 nm was fabricated from a silicon wafer with a focused ion beam. The sphere substrate friction coefficient shows a strong enhancement at a certain groove periodicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Several different parameters determine the performance of the patterned structures, including the surface chemistry and the pitch (distance between the pillars), diameter, and height of the micro-and nano-features. 6,[9][10][11] In addition, the shape of these features also contributes to their tribological and wetting behavior. Contrary to surface chemistry, the relationship between geometric parameters and friction and adhesion is quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…Several different parameters determine the performance of the patterned structures, including the surface chemistry and the pitch (distance between the pillars), diameter, and height of the micro-and nano-features. 6,[9][10][11] In addition, the shape of these features also contributes to their tribological and wetting behavior. Contrary to surface chemistry, the relationship between geometric parameters and friction and adhesion is quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used a similar experimental setup to characterise frictional properties of the SIMPS. Additionally, frictional properties of a broad variety of epoxy surfaces with different types and dimensions of the microstructure were characterised to understand the influence of two general tribological phenomena on friction: (1) molecular interaction depending on the real contact area between surfaces and (2) the interlocking of surface asperities of both contacting surfaces [3638]. This approach of investigating the contribution of different geometries and dimensions of microstructures to the friction coefficient was chosen, because the complex phenomenon of friction cannot be reduced to a single mechanism: It is rather a result of various simultaneously acting mechanisms at different scales [39–41] and this approach opens up opportunities (i) to draw conclusions on the influence of the microstructure of the snake skin on frictional properties and thereby to extend the knowledge on specific surface modifications due to the legless locomotion of snakes and (ii) to evaluate which particular features (shape, dimension, orientation) of the snake skin are worth of mimicking for technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, this microscopic contact also entails the risk that unfavorable geometrical dimensions of the contact partners cause an interlocking of the smooth friction partner in the microstructure of the counterface and therefore significantly increase the frictional force [9]. This relationship has already been investigated in the friction of technical structured surfaces [16,32]. Two crucial mechanical interactions between the contacting surfaces can be identified with the effect on the sliding coefficient of friction μ k : (1) on a nanoscale, by the influence of the real contact area; and (2) on a microscale, by the geometrical and stress-induced interlocking of the samples with the grooves of the structured countersurface.…”
Section: Discussionmentioning
confidence: 99%
“…From this, it can be concluded that the dimension of the most friction-optimized biological microstructures must reduce the real contact area of the tribological pair as much as possible without causing mechanical interlocking, both geometrically and contact-mechanically. In technical systems, Sondhauss et al [32] report that the friction coefficient for a ball microstructure contact pair could be reduced by 50%, if the interlocking could be prevented. Sondhauss et al [32] and Baum et al [16,33] show that the friction response is dominated by the geometry of the tribological pair, which is characterized by the macroscopical shape [32,34], as well as the specific geometry of the microstructural elements [35,36,37].…”
Section: Discussionmentioning
confidence: 99%